Smart Campus: Trends in cybersecurity and future development - Sánchez-Torres, Brayan; Rodríguez-Rodríguez, Jesús Alberto; Rico-Bautista, Dewar Willmer; Guerrero, César D. (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Smart Campus is an entity of any kind that uses technology and infrastructure to support and improve its processes, so people can use them better. This paper reviews the literature to contextualize the Internet of Things and its vital importance for the Smart Campus, as well as its relationship with the concepts of cybersecurity and wireless sensor network. We describe the various interrelationships, tendencies, and future development of a Smart Campus, as well as the differences and similarities with the emerging concept of Smart University. This review revealed that the Internet of Things is involved in all fields and can influence and improve the university’s processes to contribute to decision-making, technological development, and academic learning. To conclude, Smart University focuses on improving the infrastructure of universities through technology, with the main purpose of enhancing the quality of the education provided by institutions.